Exploring Theories of Socio-cultural Learning and Power as Frameworks for Better Understanding Program Planning within Community-Based Organizations - Susan J. Bracken (Adult Education Research Conference, 2008)
This essay presents a discussion of the sociocultural dimensions to learning and power in Community-based organizational program planning.
Keywords: power; socio-cultural; program planning; community-based organizations